Factors that Influence Revisist Intention to Hospital a Case Study of Balimed Hospital - Pidada, Agung Ananda Putera; Wandebori, Harimukti (Journal of Business and Management, 2016)
Abstract. This study aims to investigate the effect of Service Quality Dimensions on Customer Satisfaction, the effect of Customer Satisfaction towards Patient Revisit Intention and searching a significant relationship between variables within the biggest private hospital in Denpasar Bali, RS BaliMed. Improving Service Quality and establishing Customer Satisfaction within the hospital will increase the Patient Revisit Intention, our motive is to find out the truth regarding the statement for RS BaliMed. This study adopted several literatures for the Service Quality, Customer Satisfaction and Revisit Intention assessment.Â  In this study, 100 respondentsâ€™ data were analyzed using PLS model and finds that Assurance and Empathy from Service Quality Dimensions have positive and significant influence toward Customer Satisfaction and also followed by the findings of Customer Satisfaction has positive and significant influence toward Revisit Intention. Interestingly this study also found that Reliability, Assurance and Empathy have indirect significant influence toward Revisit Intention which considered as unique findings.Keyword: Hospital Service, Service Quality, Customer Satisfaction, Revisit Intention, Bali, Partial Least Square